Complicated Perianal Sepsis - Mitra, Abhishek (Indian J Surg, 2013)
Management of benign anorectal conditions like abscesses and haemorrhoids is usually uneventful. However, complicated perianal complications can result and have sparsely been reported in literature. Hereby, we report a series of seven patients who presented with rare sequelae like necrotising fasciitis, intraperitoneal or retroperitoneal involvement. All patients responded well to surgical management. Accordingly, complicated perianal sepsis warrants a timely and aggressive surgical intervention.